2020
DOI: 10.31235/osf.io/g9zc2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of Islamic Social Capital on Green Economic Growth in Malaysia

Abstract: This paper studies the relationship between social capital on the green growth in Malaysia, with the aim of ascertaining whether faith based social capital has a role in sustaining economic growth. The study utilizes the annual data over the period of 1970-2015. This study employs the Autoregressive Distributed Lag (ARDL) model and causality using the Vector Error Correction Model (VECM). The findings demonstrate the long and short-run associations between social capital and green growth in Malaysia. The causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The results show that green sukuk can be used as an alternative instrument with a better level of profitability and bankability than conventional products. In contrast to Campisi et al (2018), Hamid et al (2019) used the zakat instrument in their study to investigated whether zakat plays a role in supporting green economic growth in Malaysia. Using Autoregressive Distributed Lag (ARDL) approach and Vector Error Correction Model (VECM) Granger Causality test, his study revealed that in the short run, zakat has a weak impact on green economic growth.…”
Section: Green Economy and Its Relevancies With Islamic Economymentioning
confidence: 99%
“…The results show that green sukuk can be used as an alternative instrument with a better level of profitability and bankability than conventional products. In contrast to Campisi et al (2018), Hamid et al (2019) used the zakat instrument in their study to investigated whether zakat plays a role in supporting green economic growth in Malaysia. Using Autoregressive Distributed Lag (ARDL) approach and Vector Error Correction Model (VECM) Granger Causality test, his study revealed that in the short run, zakat has a weak impact on green economic growth.…”
Section: Green Economy and Its Relevancies With Islamic Economymentioning
confidence: 99%
“…Economic growth, its cyclic character, specifics in developed and developing countries, contradiction of economic growth with social development and necessity for overcoming it are studied in the works of Abdelhalim and Eldin (2019), Ali Asadullah (2019), Au (2019), Bethencourt and Kunze (2019), Burhan et al (2018), Chen et al (2018), Conroy and Weiler (2019), Cumming and Von Cramon-Taubadel (2018), Hamid et al (2019), Khan et al (2019), Kiuru and Inkinen (2019), Klofsten et al (2019), Kontogiannis et al (2019), Long and Ji (2019), Melnikas (2019), Naderi et al (2019), Pereira et al (2020), Pulido and Mora (2019), Rathnakar (2019), Sandberg et al (2019), Shastri et al (2019), Sorj and Fraga (2020), Summers et al (2019), Sun et al (2018), Sunarsih et al (2019), Xiong et al (2020), Zhang et al (2019) and Zhen and Tian (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even further, many studies have addressed the importance of going beyond formal structure of Islamic finance products, by linking maqashid sharia with social objectives such as educating individuals, establishing social justice, and achieving sustainable development (Abdullah, 2018;Amin, 2015;Chapra, 2008). Not only related to Islamic finance, the concept of maqashid sharia has also been considered by many scholars in the field of accounting (Baehaqi et al, 2020), auditing (Abd Rahman et al, 2020), business (Md Sin et al, 2015), corporate governance (Murphy & Smolarski, 2020), and economics (Hamid et al, 2019).…”
Section: Introductionmentioning
confidence: 99%